Effectiveness of facility-based personalized maternal nutrition counseling in improving child growth and morbidity up to 18 months: A cluster-randomized controlled trial in rural Burkina Faso - Nikiema, Laetitia; Huybregts, Lieven; Martin-Prével, Yves; Donnen, Phillippe; Lanou, Hermann; Grosemans, Joep; Offoh, Priscilla; Dramaix-Wilmet, Michèle; Sondo, Blaise; Roberfroid, Dominique; Kolsteren, Patrick (Public Library of Science, 2017)
The period from conception to 24 months of age is a crucial window for nutrition interventions. Personalized maternal counseling may improve childbirth outcomes, growth, and health. We assessed the effectiveness of facility-based personalized maternal nutrition counseling (from pregnancy to 18 months after birth) in improving child growth and health in rural Burkina Faso. We conducted a paired cluster randomized controlled trial in a rural district of Burkina Faso with 12 primary health centers (clusters). Healthcare providers in the intervention centers received patient-centered communication and nutrition counseling training. Pregnant women in the third trimester living in the center catchment areas and intending to stay for the next 2 years were prospectively included. We followed 2253 mother-child pairs quarterly until the child was aged 18 months. Women were interviewed about counseling experiences, dietary practices during pregnancy, and their child’s feeding practices and morbidity history. Anthropometric measurements were taken at each visit using standardized methods. The primary outcomes were the cumulative incidence of wasting, and changes in child weight-for-height z-score (WHZ). Secondary outcomes were the women’s prenatal dietary practices, early breastfeeding practices, exclusive breastfeeding, timely introduction of complementary food, child’s feeding frequency and dietary diversity, children’s mean birth weight, endpoint prevalence of stunting, and cumulative incidence of diarrhea, fever, and acute respiratory infection. All analyses were by intention-to-treat using mixed effects models. The intervention and control arms each included six health centers. Mothers in the intervention arm had a significantly higher exposure to counseling with 11.2% for breastfeeding techniques to 75.7% for counseling on exclusive breastfeeding. Mothers of infants below 6 months of age in the intervention arm were more likely to exclusively breastfeed (54.3% vs 42.3%; Difference of Proportion (DP) 12.8%; 95% CI: 2.1, 23.6; p = 0.020) as compared to the control arm. Between 6 and 18 months of age, more children in the intervention arm benefited from the required feeding frequency (68.8% vs 53.4%; DP 14.1%; 95% CI: 9.0, 19.2; p<0.001) and a larger proportion had a minimum dietary diversity (28.6% vs 22.0%; DP 5.9%; 95% CI: 2.7, 9.2; p<0.001). Birth weight of newborns in the intervention arm was on average 84.8 g (p = 0.037) larger compared to the control arm. However, we found no significant differences in child anthropometry or morbidity between study arms. Facility-based personalized maternal nutrition counseling was associated with an improved prenatal dietary practices, Infant and Young Child Feeding practices, and child birth weight. Complementary strategies are warranted to obtain meaningful impact on child growth and morbidity. This includes strategies to ensure good coverage of facility-based services and effective nutrition/care practices in early childhood.